2023
DOI: 10.1111/andr.13532
|View full text |Cite
|
Sign up to set email alerts
|

Peyronie's disease response to intralesional collagenase clostridium histolyticum therapy is independent of baseline testosterone

Douglas Schneider,
Mitchell O'Leary,
Eliad Amini
et al.

Abstract: BackgroundTestosterone plays an important role in collagen metabolism, transforming growth factor‐β1 expression, and wound healing, which are all critical factors in pathogenesis of Peyronie's disease. Some clinical studies have suggested an association between Peyronie's disease and hypogonadism.ObjectiveWe sought to investigate whether baseline total testosterone levels influence response to intralesional collagenase clostridium histolyticum in Peyronie's disease.MethodsA retrospective review of patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…To find out if any minor virulence genes were present, 84 isolates that were taken from flocks of sheep and goats were analyzed and sequenced. The findings revealed that 79 out of 84 isolates (94%), 29 out of 84 isolates (35%) had cpe detected, 28 out of 84 isolates (33%) had confirmed TpeL presence, and none of the isolates had the netB gene [20].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 97%
“…To find out if any minor virulence genes were present, 84 isolates that were taken from flocks of sheep and goats were analyzed and sequenced. The findings revealed that 79 out of 84 isolates (94%), 29 out of 84 isolates (35%) had cpe detected, 28 out of 84 isolates (33%) had confirmed TpeL presence, and none of the isolates had the netB gene [20].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 97%